APPROACHES REGARDING THE UTILITY OF THE ACCOUNTING INFORMATION - DĂNESCU, Tatiana; PROZAN, Mihaela; PROZAN, Roxana Diana (Annales Universitatis Apulensis Series Oeconomica, 2014)
In the context of the internalization and globalization of the economies, in order to efficiently respond to the different risks that could affect the credibility and the transparency of the accounting information, the carried research has proven that, there are imposed the knowledge and the implementation in practice of the financial reporting process of the leadership prerogatives afferent to a good corporate governance, of those specific to an adequate internal control and to a prospective and innovative management of these events. Starting from the multiple benefits generated by the existence of good corporate governance, under its diverse aspects and dimensions, in the carried research we have focused on the identification and instrumentation of new valences of the relationship among corporate governance, risk controlling system or process and the utility of the information from the financial statements.